Mixed Movements, International Protection and Migration: Opportunities and Challenges from the Academy - Villegas Román, Harold (2025)
Introduction: The article attempts to make a contribution to the current discussion on the importance and urgency of the University (and the Academy in a broad sense) assuming a proactive role in the analysis and approach of migratory phenomena (mixed movements) and international protection, and their various dimensions and complexities. It attempts to answer at least the following questions: Why is it important to address the issue of mixed movements from the Academy and its substantive areas such as social action? What would be the contribution in addressing the issue of migration and international protection from the University of Costa Rica as an actor in the generation of knowledge and social transformation? What would be its main opportunities and challenges? Objective: Analyze the importance of addressing human mobility phenomena from the substantive spheres of the University: teaching, research, and social action. Method: It is a qualitative research based on data on migrations and mixed movements. Results: Mixed movements must entail a series of complexities that must be addressed from an intra- and interdisciplinary academic perspective and demand an effective response from public policies from the State. [Continue reading in article]